Faktor Risiko Kejadian Relaps Pada Penderita Skizofrenia Paranoid Di RSKD Provinsi Sulawesi Selatan - Syarif, Isymiarni; Nursiah, Andi; Idris, Idris (Syntax Idea, 2020)
The research aimed to analyse the risk factors of the relapse incident on the patient with paranoid schizophrenia in Regional Specific Hospital South Sulawesi Province. This was an observational analytic research with the case control study design. Samples were as many as 76 cases who underwent relapse during the examination was conducted in the long stay unit and 76 controls who did not experience the relapse during the examination was carried out in the mental clinic. The samples were taken by using the purposive sampling technique. The data were analysed using the odds ratio test and multiple logistic regression method.The results of the research indicates that risk factors of the non-obedience to treatment are: OR = 26.168 (95%CI:10.263-68.355), health insurance OR=6.93 (95%CI:1.44-65.40) and stigma OR = 7.99 (95%CI: 3.65-17.75). Whereas the families’ support OR=1.23 (95% CI : 0.55-2.73) and the families’ psychoeducation OR = 0.75 (95% CI :0.37-1.53) are not risk factors. The non obedience on treatment OR = 21.11 (95% CI: 5.69 - 52.92) p = 0.000, represents the most risky factor towards the relapse incident on the patient with paranoid schizophrenia. Recommended patient to increased medication adherence and for families of patients to controlling in treatment and increased support and attention of paranoid schizophrenia and the government regional with Regional Specific Hospital to make regulation about health insurance of mental disorder (paranoid schizophrenia).